Management and outcomes of patients with ST-segment elevation myocardial infarction in the Western Cape Province of South Africa - Beyers, B.; Cilliers, J.; Doubell, A.; Herbst, P.; Ngarande, E.; Joubert, L.; Pecoraro, A. (SA Heart Journal, 2025)
Ischemic heart disease (IHD) is the leading cause of mortality globally and ranking among the top five causes of death in South Africa (SA). Acute coronary syndromes (ACS), particularly ST-segment elevation myocardial infarction (STEMI), contribute significantly to this burden. Despite its importance, SA lacks comprehensive ACS data, limiting the detection, estimation of cases, and understanding of patient outcomes. This study aimed to assess STEMI care within the Tygerberg Hospital (TBH) referral network in SA’s Western Cape Province. The study objectives were to evaluate the distribution of patients undergoing primary percutaneous coronary intervention (PCI) versus the pharmacoinvasive strategy, assess mortality and ACS recurrence, and investigate reasons for not performing angiography or PCI. This retrospective analysis of STEMI data from the Tygerberg Registry of ACS (TRACS) included 292 patients admitted between April and December 2020. The pharmacoinvasive strategy was employed in 65.1% of cases, with 18.5% receiving primary PCI. In-hospital and 30-day mortality rates were 5.5% and 6.9%, respectively, with a 3.1% recurrence of ACS. The study concluded that despite SA’s healthcare limitations, the pharmacoinvasive strategy, facilitated by a hub and spoke outreach model, yields outcomes comparable to international cohorts. This underscores the clinical relevance of protocolized STEMI care in resource-limited settings.